Sustainable development of energy, water and environment systems index for Southeast European cities. (1st September 2016) - Kılkış, Şiir
Abstract: Benchmarking the performance of cities across aspects that relate to the sustainable development of energy, water and environment systems requires an integrated approach. This paper benchmarks a sample of 12 Southeast European cities based on a composite indicator that consists of 7 dimensions and 35 main indicators. The composite indicator is namely the Sustainable Development of Energy, Water and Environment Systems (SDEWES) City Sustainability Index. The first three dimensions are energy consumption and climate, penetration of energy and carbon dioxide saving measures, and renewable energy potential and utilization. The last four dimensions are water and environmental quality, carbon dioxide emissions and industrial profile, city planning and social welfare, and research, development, innovation, and sustainability policy. The data collection process for the 12 cities integrates data from Sustainable Energy Action Plans and other sources. Data entries are normalized based on the Min–Max method and aggregated for a final ranking. Zagreb, Bucharest (District 1), and Ohrid are the top three cities. An average city receives a composite score of 2.69. Best practices are identified to allow cities to adopt well-rounded efforts to improve future performance. The SDEWES Index is useful to trigger learning, action, and collaboration among cities to transition to a more sustainable future. Highlights: A composite indicator is applied to benchmark Southeast European cities. The SDEWES Index consists of 7 dimensions and 35 main indicators. The top 3 cities in the sample are Zagreb, Bucharest (District 1), and Ohrid. Best practices are identified based on the top cities in each dimension. The index can be used as a metric to improve future performance.